ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP JARAK LAPORAN AUDIT - Deasy Afrilia; Tumirin Tumirin (PROCEEDING UMSURABAYA, 2022)
ABSTRACTÂ  Â This study aims to analyze the effect of profitability on the audit report distance, the effect of firm size on the audit report distance and the effect of solvency on the audit report distance. This type of research is quantitative research. The population in this study were LQ45 companies listed on the Indonesia Stock Exchange from 2016 to 2019 and were selected using the purposive sampling method. The number of samples in this study were 124 companies. The data collection method in this research is documentation. The data analysis technique used is descriptive statistics, classical assumption test, multiple linear regression analysis. The test results show that profitability does not have a significant negative effect on the distance of the audit report, the size of the company has a significant negative effect on the distance of the audit report, and Solvency has a significant negative effect on the distance of the audit report. For companies that go public, the company is expected to be responsible and obey the rules that have been set.